Voltage Oriented Control(VOC) Of The PWM Rectifier Using Active Filtering Function - Md.Mazhar-Ul-Haq, S; S.S.Tulasi Ram, Dr; JBV.Subramanyam, Dr (International Journal of Engineering and Technology, 2018)
Pulse width modulation rectifier has gathered its demand during the recent years for modification needs of the ac-dc conversion systems need for industries, customer and power grid sectors. This bidirectional converter can act as ac to dc boost rectifier with near unity power factor at the grid side along with the regulated and ripple free output voltage at the dc side. This paper deals with the evaluation of control strategy called voltage oriented control with active filtering function, Total harmonic distortion (THD),dynamic performance and parameter sensitivity is studied theoretical concept is provided and results of computer simulations are given by using mat lab.Â